To make quality cassava seeds available to farmers, It has to be a profitable business_Lawrence Kent - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Lawrence Kent describes profitability as a driver for a sustainable cassava seed systems